International politics of HIV/AIDS global disease: local pain - Seckinelgin, Hakan (Routledge, 2008)
This book examines the global governance of the HIV/AIDS epidemic, interrogating the role of this international system and global discourse on HIV/AIDS interventions. The geographical focus is Sub-Saharan Africa since the region has been at the forefront of these interventions. There is a need to understand the relationship between the international political environment and the impact of resulting policies on HIV/AIDS in the context of people's lives.